Temporary Monument - Emre Gurer (Cadernos de Arte Pública)
“What time is it?” asks artist Tyree Guyton in his mural installation at Kensington, Philadelphia. A question that asks more than what the clocks show at the present moment. As if the name of the installation, The Times –in the plural, not the singular time of the one accurate clock– asks how many times are there that order this monumental space, how many temporalities cross-cut each other at the walls of that old Kensington factory, now being a special installation within the city-wide temporary public art and history project: Monument Lab.